(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2022)
Fusarium head blight is an important disease of durum wheat which requires several fungicide treatments of seeds to achieve satisfactory control. The current study was carried out to evaluate commercially available fungicides in vitro for their efficacy against eighteen Fusarium spp. isolates collected from different fields in the north-eastern part of Algeria. The morphological and molecular characterization reveals the presence in wheat seeds of the main species complexes F. acuminatum, F. equiseti, F. avenaceum, F. solani, F. culomorum, F. incarnatum-equiseti, as well as F. tricinctum species complex and F. chlamydosporum species complex. Antifungal activity of fungicides shows that all triazoles tested have proven their effectiveness in inhibiting the mycelial growth of various strains of Fusarium tested. However, their sensitivity varies between them significantly (p<0.05) depending on the dose applied and period of exposure to each fungicide. The results showed that tebuconazole (Raxil and Tébuzole) and the combination fludioxonil + difenoconazole greatly reduced the mycelial growth of Fusarium isolates by 84.31%, 82.94%, 81.33%, respectively, as compared to difenoconazole alone (73.16%) at the recommended dose after five days of exposure. Regarding their effect on conidia germination, tebuconazole was more effective than fludioxonil + difenoconazole, which leads to deformation of cell wall structure and fragmentation of conidia. These results will provide useful information to select suitable fungicides for seed treatment and management of wheat head blight disease.